The Effect of Good Corporate Governance Implementation and Environmental Performance on Firm Value : (An Empirical Study of Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period) - Ni Made Ari Wahyuni; Anak Agung Gde Putu Widanaputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Firm value reflects investors’ perception of a company’s success, which is generally measured through its stock price. To enhance firm value, companies are required to manage their operations with integrity, efficiency, and professionalism, while safeguarding stakeholders’ interests through the implementation of Good Corporate Governance (GCG). GCG establishes a framework governing the relationships among shareholders, management, creditors, and the government in relation to their respective rights and responsibilities. In addition to GCG, environmental performance also plays an important role in influencing firm value. Effective corporate management should therefore align with the three dimensions of the Triple Bottom Line framework: profit, people, and planet. This study aims to obtain empirical evidence on the effect of Good Corporate Governance implementation and environmental performance on firm value. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A total of 41 companies were selected as samples using the purposive sampling method. Data were collected from the official IDX website (www.idx.id) and the respective companies’ official websites. The data were analyzed using multiple linear regression analysis. The results indicate that the independent board of commissioners, board of directors, and environmental performance have a positive and significant effect on firm value. However, the audit committee does not have a significant effect on firm value.